Determinants of digital inequality in universities: The case of ecuador - Duart, J. (2015)
The digital divide was initially defined by socioeconomic variables, mainly the level of family income, but now it focuses on how the Internet is used and is called digital inequality. In the case of universities, recent studies have pointed to the existence of patterns that are dependent on a variety of socioeconomic variables. This article analyses the effect that the level of family income, gender and age of students from five Ecuadorian universities has on Internet use for academic activities and entertainment purposes. In the procedure applied to a sample of 4,697 students, factor analysis was used to reduce the data, and multivariate logistic regression was used to estimate the relationships. The results show that the higher the level of family income, the better the technology use for academic activities. Regarding entertainment, the level of income does not determine the intensity of technology use, though it does determine the types of tool that students use. With reference to gender, men have a greater tendency to use technology for entertainment, but there is no difference between genders when it comes to academic uses